Evaluation of Lower Urinary Tract Symptoms suggestive of Benign Enlargement of the Prostate by Uroflowmetry and American Urological Association Symptom Score (KYAMC Journal, 2022)
Background: Uroflowmetry study is a non-invasive, simple, and inexpensive preliminary the diagnostic tool of various lower urinary tract diseases like benign prostatic hyperplasia, stricture the urethra, neurogenic bladder, etc. American Urological Association Symptom Score is the single a most important tool used in the evaluation of patients with Benign prostatic hyperplasia (BPH) and is recommended for all patients before initiation of therapy.Objectives: To evaluate lower urinary tract symptoms suggestive of Benign Enlargement of Prostate by Uroflowmetry study, measuring American Urological Symptom Score, Quality of life, and to find out correlation among Uroflowmetry parameters, age.Materials and Methods: This is a prospective study to evaluate 13 patients with lower urinary tract symptoms suggestive of benign enlargement of the prostate by performing a Uroflowmetry test. We also measured the level of symptoms by American Urological Association Symptom Score and quality of life of age group 48 to 71 years. Selected patients have gone under Uroflowmetry study recorded American Urological Association Symptom Score and quality of life by few questionnaires.Results: The mean age of the patients was 58.92+/-6.93 SD year. The mean maximum flow rate and average flow rate were found to be 16.44 and 6.99 ml/sec respectively. Voiding time and voided volume of urine was 74.53+/-44.94 SD sec, and 412.38+/- 255.66 SD ml respectively. The maximum flow rate and age were negatively correlated(R=-0.551). Time of maximum flow rate and amount of voided urine was strong positively correlated(R=0.8717, p